PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN - Rusmanto -; Indra Saputra; Lili Rahmawati (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2021)
This study was conducted to examine the effect of Investment Decisions, Funding Decisions, and Dividend Policies on the Value of Industrial Companies in the Consumer Goods Industry Sector listed on the Indonesia Stock Exchange in 2016-2018. The research method used is descriptive quantitative method, namely the number of research data is 39 data assisted by the SPSS 22 program. The results show that partially investment decisions affect firm value with a significant value of 0.000, Funding Decisions and Dividend Policy have no effect on firm value with significant values of 0.141 and 0.069 and sumultaneously Funding Decisions and Dividend Policy affect firm value with a significant value of 0.001.